2019
DOI: 10.1002/cpt.1328
|View full text |Cite
|
Sign up to set email alerts
|

From Endogenous Compounds as Biomarkers to Plasma‐Derived Nanovesicles as Liquid Biopsy; Has the Golden Age of Translational Pharmacokinetics‐Absorption, Distribution, Metabolism, Excretion‐Drug–Drug Interaction Science Finally Arrived?

Abstract: It is now established that a drug's pharmacokinetics (PK) absorption, distribution, metabolism, excretion (ADME) and drug–drug interaction (DDI) profile can be modulated by age, disease, and genotype. In order to facilitate subject phenotyping and clinical DDI assessment, therefore, various endogenous compounds (in plasma and urine) have been pursued as drug‐metabolizing enzyme and transporter biomarkers. Compared with biomarkers, however, the topic of circulating extracellular vesicles as “liquid biopsy” has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
92
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 89 publications
(172 reference statements)
0
92
0
Order By: Relevance
“…A recent study showed that CPI and CPIII can successfully predict strong and mild OATP1B‐mediated DDI in the clinic (Kunze, Ediage, Dillen, Monshouwer, & Snoeys, ). For detailed information on transporter biomarkers, please refer to other articles on the topic (Barnett et al, ; Chu et al, ; Chu, Chan, & Evers, ; Jones et al, ; Mariappan, Shen, & Marathe, ; Mueller, Sharma, Koenig, & Fromm, ; Rodrigues & Rowland, ; Shen, ; Yoshikado et al, ). Biomarkers are active research areas and future advances will help to provide new tools and insights to more accurately predict clinical DDIs.…”
Section: Mechanisms On How Perpetrators Alter Pharmacokinetics Of Vicmentioning
confidence: 99%
“…A recent study showed that CPI and CPIII can successfully predict strong and mild OATP1B‐mediated DDI in the clinic (Kunze, Ediage, Dillen, Monshouwer, & Snoeys, ). For detailed information on transporter biomarkers, please refer to other articles on the topic (Barnett et al, ; Chu et al, ; Chu, Chan, & Evers, ; Jones et al, ; Mariappan, Shen, & Marathe, ; Mueller, Sharma, Koenig, & Fromm, ; Rodrigues & Rowland, ; Shen, ; Yoshikado et al, ). Biomarkers are active research areas and future advances will help to provide new tools and insights to more accurately predict clinical DDIs.…”
Section: Mechanisms On How Perpetrators Alter Pharmacokinetics Of Vicmentioning
confidence: 99%
“…Measurement of relative changes in DMET activities with time-dependent increases and decreases in functional protein are good (i.e., induction, mechanism-based inactivation), but there is less confidence in estimating absolute abundance values. 8 3. Plasma exosomes as "liquid biopsies.…”
Section: Data Only Available In the Research Phasementioning
confidence: 99%
“…As discussed by Mikus, appropriately qualified probes and cocktails administered in microdose studies represent one avenue for collecting such data in clinical development. Rodrigues and Rowland offer a comprehensive review of the use of tissue‐derived plasma exosomes, which can be particularly valuable in generating longitudinal data on the dynamics of effects of a drug or biologic on the expression and activity of a battery of ADME proteins via ex vivo profiling. Continued forward and reverse translational research on the proposed “liquid biopsy” framework and the incorporation of the results of such investigations into PBPK models will be crucial to quantify and assess the impact of translational gaps between the ex vivo exosomal setting and in vivo native tissue setting.…”
Section: Knowledge Gaps Uncertainties and Challengesmentioning
confidence: 99%